The study of clinical profile and management of dengue fever in children - Tripathy, Asmita; Gosai, Dhara; Pathak, Gargi H.; Jadav , Mehul M. (International Journal of Contemporary Pediatrics, 2024)
Background: Dengue fever is characterized by biphasic fever, myalgia or arthralgia and rash. WHO has estimated that there are 100 million cases and 30,000 deaths worldwide. It is caused by serotypes of dengue virus and transmitted by mosquitoes of Aedes Aegypti. The aim was to study the clinical-epidemiological profile of children with dengue fever. Methods: From January 2020 to December 2020, the baseline survey was conducted in pediatrics department, Civil Hospital, Asarwa, Ahmedabad, India in which the data was confirmed dengue fever with laboratory diagnosis of serology (NS1/IgM) positive in the age group of >6 months and <12 years. Results: In a total of 127 cases of dengue, majority (52%) were in age group of 6-12 years and presented with warning signs (72%). The most common complication and hemorrhagic manifestation were dengue hepatitis (10.5%) and petechiae/purpura (29.1%). Bleeding was common when platelet count was <20000 lakh/mm3. Diagnosis was confirmed with dengue NS1 Ag (71.7%) and serum IgM (100%). Most of the patients recovered with IV fluid therapy (81.9%). Conclusions: Major admissions were in the febrile phase of the disease. NS1Ag, liver function test and ultrasonography play an important role in early diagnosis, early detection of complication and as a prognostic marker for outcome in dengue fever. The mainstay of management is adequate hydration (IV fluids). It was concluded that, prevention is better than cure of the disease in the form of integrated vector management control.